Immunocompetent, Immunized Male With Mumps, Complicated by Orchitis and Meningitis. Issue 10 (1st October 2015) - Tomich, Allison; Grubish, Lindsay; Young, Scott; Franklin, Jillian
ABSTRACT: Mumps is a rare pathology often not encountered in the emergency department setting. It is an especially unusual finding in a fully immunized individual. We present a case of a 26-year-old Army active duty male who was evaluated in the emergency department for mumps over the course of two visits. The military population is presumed fully immunized and immunocompetent, travels widely and often lives in close quarters. This case highlights the importance for providers to consider such a disease that carries a risk of significant morbidity, and rarely, mortality. A literature review was performed evaluating mumps in the vaccinated population.